2020
DOI: 10.1146/annurev-resource-101619-094219
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Strategies of Food Retailers

Abstract: Studies examining pricing outcomes in the food retail industry are complicated both by the multiproduct nature of transactions and by the presence of highly concentrated food processing and retailing industries that mediate between relatively competitive farm product markets and the consumer market. In this review, we examine theoretical and empirical evidence for retail pricing and the vertical relationships that have emerged among retailers, food manufacturers, and farmers. We first focus our analysis on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Previous literature has examined determinants of food prices (e.g., Richards and Hamilton, 2015;Volpe, Risch, and Boland, 2017;Hamilton, Liaukonyte, and Richards, 2020;Nakamura, 2008;Ghazaryan et al, 2018;Nakamura and Zerom, 2010). Factors theorized to affect food prices include input prices (Nakamura and Zerom, 2010;Volpe, Risch, and Boland, 2017;Richards and Hamilton, 2015;Hamilton, Liaukonyte, and Richards, 2020), product characteristics such as size and appearance (Ghazaryan et al, 2018), macroeconomic factors (Richards and Hamilton, 2015;Volpe, Risch, and Boland, 2017), and market power (Hamilton, Liaukonyte, and Richards, 2020;Richards, Hamilton, and Yonezawa, 2017). Similarly, it is hypothesized that input prices, product characteristics, macroeconomic factors, and firm size will have an impact on SCP prices.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous literature has examined determinants of food prices (e.g., Richards and Hamilton, 2015;Volpe, Risch, and Boland, 2017;Hamilton, Liaukonyte, and Richards, 2020;Nakamura, 2008;Ghazaryan et al, 2018;Nakamura and Zerom, 2010). Factors theorized to affect food prices include input prices (Nakamura and Zerom, 2010;Volpe, Risch, and Boland, 2017;Richards and Hamilton, 2015;Hamilton, Liaukonyte, and Richards, 2020), product characteristics such as size and appearance (Ghazaryan et al, 2018), macroeconomic factors (Richards and Hamilton, 2015;Volpe, Risch, and Boland, 2017), and market power (Hamilton, Liaukonyte, and Richards, 2020;Richards, Hamilton, and Yonezawa, 2017). Similarly, it is hypothesized that input prices, product characteristics, macroeconomic factors, and firm size will have an impact on SCP prices.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
“…Similarly, it is hypothesized that input prices, product characteristics, macroeconomic factors, and firm size will have an impact on SCP prices. While no located research has examined how firm financial performance affects food prices, this research postulates it will affect SCP prices since Trejo-Pech et al (2020) found a relationship between firm profitability measures and sugar prices, and because firms' market power throughout the food supply chain is an important consideration in explaining food prices (Hamilton, Liaukonyte, and Richards, 2020;Richards, Hamilton, and Yonezawa, 2017). Only SCP prices from publicly traded sugar-using firms were utilized so firm size and financial performance variables could be included as independent variables in the analysis.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conclude in Section 5. 1 For a recent general review on pricing strategies in food retailing, see that by Hamilton et al (2020).…”
Section: Introductionmentioning
confidence: 99%